2023
DOI: 10.1136/jnis-2023-020360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous thrombolysis on stent retriever and aspiration thrombectomy outcomes: a systematic review and meta-analysis of the randomized controlled trials

Abstract: BackgroundRisks and benefits of intravenous thrombolysis (IVT) in patients undergoing mechanical thrombectomy (MT) have been a topic of interest. However, IVT’s specific effects on stent retriever (SR) and aspiration thrombectomy (ASP) outcomes remain largely unexplored. In this meta-analysis, we aimed to investigate the effects of IVT on SR and ASP thrombectomy outcomes.MethodsIn accordance with PRISMA guidelines, a systematic literature review was conducted using Medline, Embase, Scopus, Web of Science, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent study found that intravenous thrombolysis could influence certain efficacy outcomes of stent retrievers or aspiration thrombectomy ( 29 ). However, due to a limited number of cases, we could not conduct a dedicated study to eliminate this potential confounding factor, although there may not be a significant difference in intravenous thrombolysis between the two groups in baseline data.…”
Section: Limitationmentioning
confidence: 99%
“…A recent study found that intravenous thrombolysis could influence certain efficacy outcomes of stent retrievers or aspiration thrombectomy ( 29 ). However, due to a limited number of cases, we could not conduct a dedicated study to eliminate this potential confounding factor, although there may not be a significant difference in intravenous thrombolysis between the two groups in baseline data.…”
Section: Limitationmentioning
confidence: 99%